2021
DOI: 10.1096/fj.202100300r
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycans on lymphatic endothelial cells augment interactions with Siglec‐1 (CD169) of lymph node macrophages

Abstract: Cellular interactions between endothelial cells and macrophages regulate macrophage localization and phenotype, but the mechanisms underlying these interactions are poorly understood. Here we explored the role of sialoglycans on lymphatic endothelial cells (LEC) in interactions with macrophage-expressed Siglec-1 (CD169). Lectin-binding assays and mass spectrometric analyses revealed that LEC from human skin express more sialylated glycans than the corresponding blood endothelial cells. Higher amounts of sialyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…Recently, we transcriptionally characterized LN-resident macrophages and revealed that CLEC-2 is largely absent from MSMs [ 70 ], suggesting the participation of alternative podoplanin receptors in mediating MSM interactions, such as CD44 or the recently identified CD177 [ 71 ] that are more highly expressed in MSMs at steady-state [ 70 ]. In addition, podoplanin might mediate sinusoidal macrophage adhesion to LECs through attached sialoglycans binding to CD169 [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we transcriptionally characterized LN-resident macrophages and revealed that CLEC-2 is largely absent from MSMs [ 70 ], suggesting the participation of alternative podoplanin receptors in mediating MSM interactions, such as CD44 or the recently identified CD177 [ 71 ] that are more highly expressed in MSMs at steady-state [ 70 ]. In addition, podoplanin might mediate sinusoidal macrophage adhesion to LECs through attached sialoglycans binding to CD169 [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mere fact that the number of CD169 + macrophages is increased in mildly altered skeletal muscle tissue is remarkable. CD169 + macrophages are increased in idiopathic inflammatory myopathies ( 54 ), indicating a prominent role in type I Interferon-related immune processes ( 55 ), and recent studies emphasized their highly specific functional programmes and important roles as border-associated cells at blood vessel/parenchymal interfaces ( 56, 57 ). CD169 + macrophages have further been implicated in antiviral defense, being the primary cell infected and able to capture viral particles in the blood and subsequently presenting them to B cells ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sinusoidal LECs are crucial for promoting the differentiation of LN-resident macrophages [61][62][63]. Genetically engineered mice have been especially important for dissecting the roles of key molecules mediating LEC-macrophage interactions: conditional deletion of colony stimulating factor-1 (CSF-1) production by LECs (Prox1 creERT2 Rosa tdTOM Csf1 flox/flox mice) leads to a marked reduction in the number of subcapsular and medullary sinus macrophages compared to wildtype controls, demonstrating the importance of CSF-1 in maintaining the macrophage niche in lymphatic sinuses [61].…”
Section: Macrophagesmentioning
confidence: 99%
“…In addition, Rank deficiency in LECs (Rank ΔProx1 mice) during normal embryogenesis as well as during vesicular stomatitis virus infection in adult mice reduces the number of sinus macrophages [62]. Moreover, interactions between sialoglycans, which are highly displayed on SCS floor LECs, and Siglec-1/ CD169 on macrophages, are crucial for regulating macrophage localization, as well as the proinflammatory phenotype of mouse SCS LECs [63]. Thus, the molecular interactions between macrophages and LECs appear to be important for the proper anatomical localization and function of macrophages.…”
Section: Macrophagesmentioning
confidence: 99%